Substrate Integrated Waveguide Leaky-Wave Antenna Conforming to Conical Shape Surface - W. N. Huang; Y. J. Cheng; H. Deng (International Journal of Antennas and Propagation)
A conical conformal leaky-wave antenna based on substrate integrated waveguide (SIW) technology is proposed and demonstrated in this paper. This antenna conforms to a conical shape surface with the angle of 40°. It has a narrow beam that scans from 80° to 97° with varying frequency (34 GHz~37 GHz). Both conformal and nonconformal antennas are fabricated through the standard PCB process. Their performances are compared within the desired frequency.